2021
DOI: 10.1007/s00221-021-06146-0
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory contribution in visuospatial orientation: an interaction between neck and trunk proprioception

Abstract: A coherent perception of spatial orientation is key in maintaining postural control. To achieve this the brain must access sensory inputs encoding both the body and the head position and integrate them with incoming visual information. Here we isolated the contribution of proprioception to verticality perception and further investigated whether changing the body position without moving the head can modulate visual dependence—the extent to which an individual relies on visual cues for spatial orientation. Spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Visual cues provide stable references for verticality, for example from buildings and trees, while vestibular signals indicate the location of the head with respect to gravity via the otoliths [12,13]. In addition, proprioceptive and somatosensory signals about the position of the neck and the trunk indicate the position of the longitudinal body axis (i.e., the 'idiotropic vector [14]') and contribute to a prior that the head is usually upright [10,[14][15][16][17][18][19]. Previous studies have demonstrated that tilting either the head or the trunk biases the Subjective Visual Vertical (SVV, [20]).…”
Section: Introductionmentioning
confidence: 99%
“…Visual cues provide stable references for verticality, for example from buildings and trees, while vestibular signals indicate the location of the head with respect to gravity via the otoliths [12,13]. In addition, proprioceptive and somatosensory signals about the position of the neck and the trunk indicate the position of the longitudinal body axis (i.e., the 'idiotropic vector [14]') and contribute to a prior that the head is usually upright [10,[14][15][16][17][18][19]. Previous studies have demonstrated that tilting either the head or the trunk biases the Subjective Visual Vertical (SVV, [20]).…”
Section: Introductionmentioning
confidence: 99%